(untitled) (International Journal of Engineering and Computer Science, 2017)
It is difficult to determine the structures like caves where the humans cannot enter. Remotely controlled car can enter in such spaces and can give a user the experience of structure he may be entering, before he could even get into it. The idea behind the proposed system is to show the approximate structure of the area on the system. The user can then study and analyze it for any changes that would occur. We have put forth a method to plot the structure of the terrain using ultrasonic sensors along with the use of Arduino to accomplish this purpose. This paper improvises the way in which it is accomplished.